Phonological competition during spoken-word recognition in infants and adults - Spangenberg, M (2019)
This thesis examines how phonological information mediates visual attention in adults and 2-year-olds. It makes use of the Visual World Paradigm during which participants see images on a screen and hear phonologically related or unrelated words in order to investigate the time course of processing of phonological information. It further examines how the amount of time observers are given to look at the images before hearing the spoken word (pre-naming time) and the concept of implicit naming (silent labelling of the images) modulate observers' processing strategies. Findings from Experiments 1-4 reveal that adults employ continuous processing strategies whereby different lexical entries compete with each other in parallel until the most relevant entry is selected. In contrast to previous findings (Huettig & McQueen, 2007), results from Experiments 1 and 2 show that adults' visual attention is mediated by phonological information even with a very short pre-naming time of 200ms suggesting that silent labeling of the images before hearing the auditory input is not required for this modulation. Experiments 3 and 4 demonstrate that when given a pre-naming phase, adults make use of processing strategies focusing on the first phoneme of words whereas without any pre-naming time, they rely more on processing strategies taking into account the overall similarity of words. Experiment 6 shows that while infants' visual attention does not seem to be mediated by phonological information when using real words - possibly due to the activation of lexical information - 2-year-olds seem to place greater importance on the overall similarity between words rather than on the onset of spoken words when presented with pseudowords. Continuous and incremental models of spoken-word recognition are contrasted and the role of implicit naming and the length of the pre-naming time is discussed in relation to these models. Finally, it is discussed how assumptions made by the Featurally-Underspecified Lexicon account (Lahiri & Reetz, 2010) might feed into the extension of continuous processing models such as the TRACE model (McClelland & Elman, 1986) (Experiment 7).